CYSTIC DUCT LEAKAGE AFTER LAPAROSCOPIC CHOLECYSTECTOMY: DEMONSTRATED BY SPIRAL CT CHOLANGIOGRAPHY - SUCHATO, Chirote; PEKANAN, Patchrin; KUMPOLPUNTH, Sopon; DANGKHAO, Wasan (The ASEAN Journal of Radiology, 2023)
Bile leakage from the cystic duct stump, was demonstrated by spiral CT cholangiography. The patient was 55 years old and was underwent laparoscopic cholecystectomy. Spiral CT cholangio- graphy is a simple and quick imaging study to detect such leakage.